REQUIREMENTS FOR TRANSFORMATIONAL CLOTHING IN POSTMODERN SOCIETY - Dovranova Oysulton Dovrankulovna; Shamsiyeva Marjona Uchqun qizi (Journals Park Publishing, 2025)
The fashion with the transition of humanity into the information sphere, demonstrates other principles of the society life and establishes new conditions for the personality self-realization in it. The rapid growth of scientific achievements, paradoxically, exacerbates the problem of «human» interpersonal relationships. The cardinal changes of the fashion from the end of the 19th to the 20th century, occurred with the loss of spirituality, particularly affected the inner world of the personality. A representative culture in the sphere of costume design, in terms of the post-human manifestation, has undergone a tremendous shift under the influence of established social transformations. The analysis of the philosophical discourse of postmodernism culture, affecting modern fashion and human existence is carried out.
Keywords: Fashion, postmodernism, transformation, communication, information society, virtual reality.